TINGKAT KECEMASAN ATLET BOLA VOLI SEBELUM BERTANDING - Sendi Hendra; Eka Supriatna; Edi Purnomo (Universitas Tanjungpura, 2021)
AbstrakVolleyball game factors to achieve maximum performance is not only required physical ability, technique and tacrics but not lose importance role psichic or anxiety. Anxiety synonymous with negative feelings. Everyone has different levels of anxienty depending on the cause, this difference depends on each athlete in handling anxiety experienced. This research aims to determine how high the level of anxiety volleyball athletes before competing. This research design uses a descriptive method, with survey research.The sample in this research using technique sampling jenuh with total 87 people. The data collection technique used questionnaire the Sprot Anxiety Scate 2 (SAS). The data analysis technique used in this research is a desciptive analysis with percentage. The results showe that the level of anxiety volleyball athletes before competing, somatic factor 40%, while the concentration factor 25%, and the worry factor 35%Keywords: Anxiety, volleyball.